Analysis of Students Knowledge and Preparedness for Flooding at Panca Budi Middle School, Medan - Maharani, Adelia Putri; Susilawati; Syahlin, Fazra Ulya; Alfiyah, Shafira; Gultom, Zalfa Syahirah (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
A disaster is an event or series of events that threaten and disrupt people's lives and livelihoods, which can be caused by natural, non-natural, or human factors. Natural disasters such as earthquakes, floods, and hurricanes can cause death, physical injury, and even mental health disorders, especially in vulnerable groups such as children, women, and the elderly. Panca Budi Junior High School, Medan, is located in an area frequently affected by flooding, so the school's environmental conditions require students to have adequate knowledge and preparedness to face the potential for such disasters. The lack of student understanding regarding the causes, impacts, and steps to deal with floods is the main background for the need for disaster education in the school environment. This study aims to analyze the level of student knowledge and preparedness before and after being provided with counseling on flood mitigation. The method used was a quasi-experimental with a one-group pre-test and post-test design, involving 50 students selected through multistage sampling. The research instrument was a 20-item knowledge and preparedness questionnaire using the Guttman scale. The results of the study showed a significant increase after the educational intervention was given, where the average pre-test score of 9.48 increased to 16.46 in the post-test. The Wilcoxon Signed Rank Test yielded a Z value of –6.125 with p = 0.000 (p < 0.05), which proves that the counseling has a significant effect on increasing students' knowledge and preparedness. In conclusion, disaster counseling is effective in improving the understanding and preparedness of Panca Budi Medan Middle School students in facing flood risks.